Biodiesel: Analysis of production, efficiency, economics and sustainability in Nigeria - Chidiebere Millicent Igwebuike (Clean Technologies and Recycling, 2023)
Biodiesel, a type of biofuel is a low-carbon substitute for fossil fuels. It has a flash point of 100 to 170 ℃ and an energy content of 33 MJ/L and can help to mitigate climate change by reducing greenhouse gas emissions. This review looked at the properties and benefits of biodiesel and the current situation of Nigeria's biodiesel industry. It examined the various feedstocks, including first-, second-, third- and fourth-generation options, and assesses their availability, viability and cost. The assessment analyzed the industry's challenges as well as the policies and incentives for biodiesel production, and use in Nigeria. Taking into account the cost of production, distribution and use, as well as prospective government subsidies and tax credits, the economic viability of biodiesel was also evaluated. Generally, the biodiesel industry in Nigeria has the potential for growth with the right assistance from the government and private sector.